PEMANFAATAN MEDIA SOSIAL DALAM PENGAJARAN AGAMA KRISTEN: MEMAHAMI DAMPAKNYA TERHADAP PEMBENTUKAN IDENTITAS ROHANI - Daniel Hutabarat; Tiurma Septiani; Damayanti Nababan (CV. Denasya Smart Publisher, 2024)
The use of social media in teaching Christianity has become a significant topic in the current digital era. This article aims to understand the impact of social media on the formation of individual spiritual identity. Social media has an important role in expanding access to information, building religious communities, and facilitating interaction between Christians. However, there are negative impacts that need to be considered, especially for Christian teenagers, such as reduced study time, impaired concentration at school, decreased morale, unwise spending of money, and negative impacts on health. This article advocates wise use of social media by managing time, selecting useful content, and prioritizing faith growth. A holistic approach in Christian religious education is needed to integrate spiritual values ​​with a deep understanding of technology. Thus, the use of social media can be optimized as a tool that supports spiritual growth and the formation of a strong Christian identity.